Thai Cinema: The Complete Guide - Ainslie, Mary J (I. B. Tauris & Company, Limited, 2018)
Cover -- Title -- Copyright -- Contents -- List of Illustrations -- List of Contributors -- Introduction -- 1. Key Directors -- Nonzee Nimibutr -- Ratana Pestonji -- Prachya Pinkaew -- Banjong Pisanthanakun -- Pen- Ek Ratanaruang -- Wisit Sasanatieng -- Yuthlert Sippapak -- Cherd Songsri -- Apichatpong Weerasethakul -- Chatrichalerm Yukol -- 2. Key Early Productions -- Miss Suwanna of Siam / Nang Sao Suwan (1923) -- Double Luck / Chok Song Chan (1927) -- A Fable from an Uncle: The Magical Ring / Nithan Khong Lung Rueang Waen Wiset (1929) -- The King of the White Elephant / Phrachao Changphueak (1940) -- Santi- Vina (1954) -- Country Hotel / Rong Raem Narok (1957) -- Mae Nak Phra Khanong (1959) -- Black Silk / Phrae Dam (1961) -- Money Money Money / Ngoen Ngoen Ngoen (1965) -- Sugar Is Not Sweet / Namtan Mai Wan (1965) -- Ngu Phi (1966) -- Pisat Saneha (1969) -- Monrak Lukthung (1970) -- Golden Eagle / Insi Thong (1970) -- Tone (1970) -- Ghost of Guts Eater / Krasue Sao (1973) -- His Name Is Khan / Khao Chue Kan (1973) -- The Scar / Phaenkao (1977) -- Mountain People / Khon Phukao (1979) -- The Adventure of Sudsakorn / Sudsakorn (1979) -- Son of the Northeast / Luk Isan (1982) -- Butterfly and Flowers / Phisuea Lae Dokmai (1985) -- The Elephant Keeper / Khon Liang Chang (1987) -- Boonchu Phu Narak (1988) -- Ban Phi Pop (1989) -- Song of Chaophraya / Nong Mia (1990) -- Somsri #422R (1992) -- A Couple in Two Worlds / Khu Thae Song Lok (1994) -- Muen and Rid / Amdaeng Muean Kap Nai Rit (1994) -- Red Bike Story / Chakkrayan Si Daeng (1997) -- 3. New Thai Cinema -- Fun Bar Karaoke / Fan Ba Karaoke (1997) -- 6ixtynin9 / Rueang Talok 69 (1999) -- Tears of the Black Tiger / Fa Thalai Chon (2000) -- Transistor Love Story / Monrak Transistor (2001) -- Mekhong Full Moon Party / Sip Ha Kham Duean Sip Et (2002).